NBEA: Developmental disease gene with early generalized epilepsy phenotypes. Issue 5 (25th October 2018) - Mulhern, Maureen S.; Stumpel, Constance; Stong, Nicholas; Brunner, Han G.; Bier, Louise; Lippa, Natalie; Riviello, James; Rouhl, Rob P. W.; Kempers, Marlies; Pfundt, Rolph; Stegmann, Alexander P. A.; Kukolich, Mary K.; et al.
Abstract : NBEA is a candidate gene for autism, and de novo variants have been reported in neurodevelopmental disease (NDD) cohorts. However, NBEA has not been rigorously evaluated as a disease gene, and associated phenotypes have not been delineated. We identified 24 de novo NBEA variants in patients with NDD, establishing NBEA as an NDD gene. Most patients had epilepsy with onset in the first few years of life, often characterized by generalized seizure types, including myoclonic and atonic seizures. Our data show a broader phenotypic spectrum than previously described, including a myoclonic‐astatic epilepsy–like phenotype in a subset of patients. Ann Neurol 2018;84:796–803